Design and development of a three-phase off-board electric vehicle charger prototype for power grid voltage regulation - Yong J.Y.; Fazeli S.M.; Ramachandaramurthy V.K.; Tan K.M. (Elsevier Ltd, 2023)
Automotive batteries; Digital signal processors; Electric power system control; Electric power transmission networks; Electric vehicles; Quality control; Reactive power; Signal processing; Solar cells; Vehicle-to-grid; Voltage control; Voltage regulators; Auxiliary power supply; Battery chargers; Control performance; Design and Development; Experimental prototype; Power conversion; Power quality standards; Reactive power compensation; Charging (batteries); design method; electric field; electric vehicle; electricity supply; experimental study; quality control; resource development; signal processing; standard (regulation)